HIV-care access among people with incarceration experience in St. Petersburg, Russia. (31st August 2017) - Ruiz, Monica S; Heimer, Robert; Levina, Olga S; Badosova, N V; Rassokhin, Vadim V; Belyakov, Andrey N; Belyakov, Nikolai A
Abstract: Background: Little is known about the clinical care experiences of HIV-infected persons in St. Petersburg who have experience with incarceration. To address this question, we conducted a capture-recapture study to identify individuals who had been diagnosed with HIV infection while incarcerated and who subsequently presented for medical care in St. Petersburg, Russia following release from prison. Methods: We matched 292 HIV-positive prisoners tested by the prison system in 2010 to the medical records at the St. Petersburg AIDS Center in the following 4 years. Results: The data analysis shows that as many as half of HIV+ prisoners fail to seek treatment in the community upon release. Of those who had sought care post-release, only 36% were receiving HAART. Of the 109 individuals for whom tuberculosis testing was indicated post-release, 36.7% were found to be reactive. Conclusion: Despite the limitations of the data, this study is the first of its kind to review records documenting HIV care among prisoners in Russia post-incarceration. In addition to providing important descriptive information about this marginalized population, the findings from this study highlight areas where HIV control efforts could be improved in order to address the HIV epidemic in the Russian Federation.